MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN BELAJAR SISWA MELALUI CONTEXTUAL TEACHING AND LEARNING - Mahrufi, Yuniar Elmanura; Nurita, Tutut (PENSA E-JURNAL: PENDIDIKAN SAINS, 2024)
This study aimed to determine the effect of the Contextual Teaching and Learning (CTL) approach on improving learning outcomes, learning activeness, and student responses to vibration, wave, and sound materials. This study is a quasi-experiment research with a nonequivalent control group design. The subjects in this study involved all class VIII students at one of the Islamic Junior High Schools in Situbondo Regency, totaling 62 students. The sample in this study was taken using a saturated sampling technique, where 31 class VIII-A students were selected as the experimental group and 31 class VIII-B students were selected as the control group. Data collection instruments used observation sheets, study test sheets, and response questionnaire sheets. The data analysis techniques used in this research are quantitative descriptive data analysis and qualitative data analysis. The observations of learning implementation showed an average of 96.33% and student activity showed an average of 81.88% with each in the very good category. Through the contextual teaching and learning approach, student learning outcomes experienced an increase in the N-gain score of 76.88% or 0.77 in the high category. Student responses to the contextual teaching and learning approach showed an average of 97.09% in the very good category. So, a conclusion can be drawn that the contextual teaching and learning approach improved learning outcomes and student learning activity.